The Exosomal/Total α-Synuclein Ratio in Plasma Is Associated With Glucocerebrosidase Activity and Correlates With Measures of Disease Severity in PD Patients - Cerri, Silvia; Ghezzi, Cristina; Sampieri, Maria; Siani, Francesca; Avenali, Micol; Dornini, Gianluca; Zangaglia, Roberta; Minafra, Brigida; Blandini, Fabio (Frontiers in Cellular Neuroscience, 2018)
Intensive research efforts in the field of Parkinson’s disease (PD) are focusing on identifying reliable biomarkers which possibly help physicians in predicting disease onset, diagnosis, and progression as well as evaluating the response to disease-modifying treatments. Given that abnormal alpha-synuclein (α-syn) accumulation is a primary component of PD pathology, this protein has attracted considerable interest as a potential biomarker for PD. Alpha-synuclein can be detected in several body fluids, including plasma, where it can be found as free form or in association with exosomes, small membranous vesicles secreted by virtually all cell types. Together with α-syn accumulation, lysosomal dysfunctions seem to play a central role in the pathogenesis of PD, given the crucial role of lysosomes in the α-syn degradation. In particular, heterozygous mutations in the GBA1 gene encoding lysosomal enzyme glucocerebrosidase (GCase) are currently considered as the most important risk factor for PD. Different studies have found that GCase deficiency leads to accumulation of α-syn; whereas at the same time, increased α-syn may inhibit GCase function, thus inducing a bidirectional pathogenic loop. In this study we investigated whether changes in plasma total and exosome-associated α-syn could correlate with disease status and clinical parameters in PD and their relationship with GCase activity. We studied 39 PD patients (mean age: 65.2 ± 8.9; men: 25), without GBA1 mutations, and 33 age-matched controls (mean age: 61.9 ± 6.2; men: 15). Our results showed that exosomes from PD patients contain a greater amount of α-syn compared to healthy subjects (25.2 versus 12.3 pg/mL, p<0.001) whereas no differences were found in plasma total α-syn levels (15.7 versus 14.8 ng/mL, p=0.53). Moreover, we highlighted a significant increase of plasma exosomal α-syn/total α-syn ratio in PD patients (1,69 versus 0,89, p<0.001), which negatively correlates with disease severity (p= 0.014). Intriguingly, a significant inverse correlation between GCase activity and this ratio in PD subjects was found (p=0.006). Additional and large-scale studies comparing GCase activity and pathological protein levels will be clearly needed to corroborate these data and determine whether the association between key players in the lysosomal system and α-syn can be used as diagnostic or prognostic